Solid waste minimization in Malaysia - Alias, Fatma Sabariah; Abd Manaf, Latifah; Ariffin, Mariani; Abdullah, Sabrina Ho (Universiti Putra Malaysia Press, 2018)
Malaysia has taken initiative in enforcing the Solid Waste Management and Public Cleansing Act 2007 (Act 672) since 2011 to ensure the uniformity of law relating to the solid waste management and public cleansing. Despite the alarming issues on the increasing of solid waste generation, Malaysian government has made solid waste separation at source as mandatory starting 1st September 2015 at eight states. Solid waste separation at source has been seen as the best practice of solid waste minimization where it eliminates and reduces the amount of solid waste produced by the society. The government has taken seriously in solid waste separation at source as the lifespan of disposal site has been decreased and limited space for the new disposal site due to the increasing cost of solid waste management. Hence, to overcome the increasing of solid waste generation, an integrated solid waste minimization through recycling should be implemented as it is involved in minimizing resource and offers the best outcome for the environment. Thus, this paper discussed the overview of solid waste minimization in Malaysia and the stakeholder’s role and their obstacles in solid waste minimization to attract the public participate in reducing the solid waste generation as an efficient solid waste management. A proper solid waste management ensures a sustainable development of Malaysia in terms of health, socio-economy and environment respectively towards Malaysian Vision of 2020.